Power and purpose in space. - Zubrin, R.
Wood, wind, water, coal, oil, gas, and nuclear energy: of those major power sources, only one-nuclear energy-can work in space. In this paper, the author argues that exploration of the Solar System will only get serious when spacecraft can exploit the power of the atom.
Keywords: Nuclear energy; Nuclear-powered spacecraft; Radioisotope thermoelectric generators; Space power